A new name and considerations on Spigelia multispica Steud. and its varieties - Zappi, Daniela C. (Phytotaxa, 2016)
Upon examining material of Loganiaceae for the Brazilian state of Pará, available specimens of Spigelia multispica Steud. were reassessed. In the process, this name and one heterotypic variety were confirmed as synonyms of the older name Spigelia hamellioides Kunth, which had not previously been reported from Brazil, whereas a new name, Spigelia spruceana Zappi, is proposed for Spigelia multispica var. angustifolia Prog.